QIP, a Component of the Vegetative RNA Silencing Pathway, Is Essential for Meiosis and Suppresses Meiotic Silencing in Neurospora crassa - Lee, Dong Whan (Genetics Society of America, 2010)
Among the processes that play essential roles in both genome defense and organism survival are those involved in chromosome comparison. They are acutely active in the meiotic cells of Neurospora crassa, where they evaluate the mutual identity of homologs by a process we call trans-sensing. When nonsymmetrical regions are found, they are silenced. The known molecular components of this meiotic silencing machinery are related to RNA-dependent RNA polymerases, Argonautes and Dicers, suggesting that the mechanisms of how heterologous chromosomal regions are silenced involves, at some stage, the production of small interfering RNAs. Neurospora has two active and clearly distinct RNA interference pathways: quelling (vegetative specific) and meiotic silencing (meiosis specific). Both pathways require a common set of protein types like RNA-dependent RNA polymerases, Argonautes and Dicers. In this work we demonstrate the involvement of quelling defective-2 interacting protein (qip(+)), a Neurospora gene whose function is essential to silencing by quelling, in meiotic silencing, and normal sexual development. Our observations reinforce the molecular connection between these two silencing pathways.